Tinjauan Hukum terhadap Tindak Pidana Penadah Spido Meter Oleh Karyawan PT. Prima Jaya Perkasa - Nasution, Syahra; Hasibuan, A. Lawali; Munthe, Riswan (Universitas Medan Area, 2024)
The collector is an act of buying, renting, exchanging, receiving, pawning, transporting, keeping, or hiding an object or taking profit from the proceeds of an object known or suspected to have been obtained from a crime and is punishable by a maximum imprisonment of four years. The research method used in this research is normative research method and direct data collection is obtained from related agencies, namely the Medan District Court, and from library materials. Factors causing the criminal act of collecting spido meters by employees of PT. Prima Jaya Perkasa based on decision No. 2811 / Pid.B / 2016 / PN.MDN, which is known in this case, shows that the criminal act of using spido meter is caused by internal factors consisting of individual, economic, educational, and religious factors. The next factor is due to external factors consisting of environmental factors and technological and cultural development factors. The panel of judges sentenced the defendant to imprisonment for 1 (one) year and 6 (six) months. The countermeasures carried out in the criminal act of detention are repressive and preventive measures.